The effect of Substitution of Pumpkin Flour on Wheat Flour and Concentration of Yeast on Doughnut - Meskayani Tamba; Sentosa Ginting; Lasma Nora Limbong (Jurnal Rekayasa Pangan dan Pertanian, 2014)
This research was aimed to know the effect of substitution of pumpkin flour on wheat flour that still acceptable, concentration of yeast to produce the best characteristic of doughnut and to introduce a new pumpkin product. This research was conducted using a completely randomized design with two factors, namely substitution of pumpkin flour on wheat flour; 15:85, 30:70, 45:55 and 60:40 and concentration of yeast; 1,0%, 1,5%, 2,0% and 2,5%. The parameters analyzed were water content, ash content, fat content, protein content, fiber content, carbohydrate content, color, flavour, taste and texture. The results showed that the effect of substitution of pumpkin flour on wheat flour had highly significant effect on water content, ash content, fat content, protein content, fiber content, carbohydrate content, volume, color, flavour, taste and texture. Concentration of yeast gave highly significant effect on protein content, volume, flavour, taste and texture and provided no effect on water content, ash content, fat content, fiber content, carbohydrate content and color. Interactions of the two factors gave highly significant effect on protein content, volume, flavour and taste and had significant effect on texture and provided no effect on water content, ash content, fat content, fiber content, carbohydrate content and color. The effect of substitution of pumpkin flour on wheat flour of 30:70 and concentration of yeast of 2,0% produce the best quality of doughnut. Keywords: doughnut , pumpkin flour, substitution, yeast.